KEPUASAN IBU PASCA SALIN YANG MENDAPATKAN LAYANAN PAIN RELIEF PADA KALA I DI RUMAH SAKIT UMUM BALI ROYAL TAHUN 2023 - Ariyanti, Ni Wayan; Darmapatni, Made Widhi Gunapria; Sriasih, Ni Gusti Kompiang (ARCHIVE OF COMMUNITY HEALTH, 2024)
Providing non-pharmacological therapy to reduce pain in the first stage of labor, namely relaxation techniques. The aim of the study was to determine the satisfaction of postpartum mothers who received pain relief services in the first stage at Bali Royal General Hospital in 2023. This type of research was descriptive with a cross sectional approach. The sample size is 35 people taken by accidental sampling. Retrieval of data using a questionnaire. The results of the study provided pain relief services at Bali Royal Hospital in 2023, namely relaxation techniques 62.9%, deep breathing 88.6%, gymball 45.7%, massage 60%, and warm compresses 40%. at RSU Bali Royal in 2023 based on patient satisfaction dimensions including very satisfied tangibles (65.7%), satisfied reliability (57.1%), very satisfied responsiveness 54.3%, satisfied assurance (57.1%) and very empathetic satisfied 65.7%. Conclusion The most widely used pain relief service is deep breathing and the least is warm water compresses. Based on the tangibles dimension, the reliability dimension, the responsiveness dimension, the assurance dimension, and the empaty dimension most of the respondents felt very satisfied. The highest dimension of satisfaction is the dimensions of tangibles and empathy while the lowest is responsiveness. Keywords:  Maternal satisfaction, Pain reliever, First stage of labor